Ultrasound Molecular Imaging for Multiple Biomarkers by Serial Collapse of Targeting Microbubbles with Distinct Acoustic Pressures. Issue 22 (2nd May 2022) - Li, Zhenzhou; Lai, Manlin; Zhao, Shuai; Zhou, Yi; Luo, Jingna; Hao, Yongsheng; Xie, Liting; Wang, Yaru; Yan, Fei
Abstract: Ultrasound molecular imaging (UMI) has shown promise for assessing the expression levels of biomarkers for the early detection of various diseases. However, it remains difficult to simultaneously image multiple biomarkers in a single systemic administration, which is important for the accurate diagnosis of diseases and for understanding the dynamic intermolecular mechanisms that drive their malignant progression. The authors develop an ultrasound molecular imaging method by serial collapse of targeting microbubbles with distinct acoustic pressures for the simultaneous detection of two biomarkers. To test this, αv β3 ‐targeting lipid microbubbles (L‐MBα ) and VEGFR2‐targeting lipid‐PLGA microbubbles (LP‐MBv ) are fabricated and simultaneously injected into tumor‐bearing mice at 7 and 14 days, followed by the low‐intensity acoustic collapse of L‐MBα and high‐intensity acoustic collapse of LP‐MBv . The UMI signals of L‐MBα and LP‐MBv are obtained by subtracting the first post‐burst signals from the first pre‐burst signals, and subtracting the second post‐burst signals from the first post‐burst signals, respectively. Interestingly, the signal intensities from UMI agree with the immunohistochemical staining results for αv β3 and VEGFR2. Importantly, they find a better fit for the invasive behavior of MDA‐MB‐231 breast tumors by analyzing the ratio of αv β3 integrin to VEGFR2, but not the single αv β3 or VEGFR2 levels. Abstract : An innovative ultrasound molecular imaging method is successfully demonstrated for the simultaneous imaging of multiple biomarkers in a single systemic administration by the serial collapse of targeting microbubbles with distinct acoustic pressures which would be important for the accurate diagnosis of diseases and for understanding of the dynamic intermolecular mechanisms that drive their malignant progress.